Respon dan Usulan Dosen terhadap Implementasi Kurikulum Program Sudi PGMI - Abu Amar (IBTIDA, 2022)
This study aims to find out the responses and suggestions of PGMI lecturers regarding the implementation of the KKNI curriculum for the PGMI STIT Al-Fattah study program in 2019. Data collection was obtained through questionnaires, documentation and interviews. Conclusions are obtained through the application of qualitative descriptive and content analysis content. The conclusion of this study is that the response of lecturers to the feasibility of the PGMI curriculum as much as 36% strongly agree, 55% agree, disagree 9% and strongly disagree as much as 1%. This means that the majority or 90% of study program lecturers assess that the study program curriculum is good, while 10% say it is not good and needs improvement. Lecturers' suggestions for curriculum implementation are the need to improve the completeness of curriculum documents, as well as aspects of operational details in the elements of learning and assessment, the need for the involvement of all study program lecturers in carrying out periodic evaluations at the end of each semester on the achievement of learning outcomes.